Factors Affecting Academic Staff Job Satisfaction in Malaysia Private University College - Tan, Yin (2010)
Organization has concerned about job satisfaction of employees today due to job satisfaction have significant relationship with employees behavior. Employees with high job satisfaction are less likely to quit from their job. The purpose of this research was to determine the factors affecting academic staff job satisfaction in Malaysia private university colleges. The factors include motivation factor and hygiene factors include supervisor, working condition and pay. Moreover, this research studied the relationship between personal demographic characteristics (gender, age, marital status) and academic staff job satisfaction. The study will focus towards the academic staff population of Malaysian private university colleges and their perception towards job satisfaction in their workplace. This research was used quantitative methods methodologies as the main methods for investigation of academic staffs’ job satisfaction in Malaysian private university colleges. In order to collect primary data, a self-completed questionnaire was designed and gave to academic staffs who are working in three private university colleges in Malaysia. The findings show that both motivation factors and hygiene factors have a significant effect on academic staffs’ job satisfaction in Malaysian private university college. The findings also show that there is a significant relationship between personal demographic characteristics except marital status. This study can serve as a model to be adopted for years to as decisive factors for job satisfaction of academic staff in Malaysia private university colleges.